The Relationship Between Self-Control and Academic Procrastination Among Students - Rokiyah, Rokiyah; Dewi, Ratna Sari; Valyediniti, Velya (Program Studi Bimbingan dan Konseling Islam, 2025)
Procrastination is a problem that everyone experiences and can have negative consequences if it continues. One factor that is thought to play a role in procrastination is self-control. Individuals with low self-control tend to procrastinate, while individuals with high self-control are better able to manage their time and fulfill their responsibilities. The purpose of this study is to determine the relationship between self-control and academic procrastination among college students. This study uses a quantitative method with a correlational research design. This study examined guidance and counseling students at Sriwijaya University and involved 367 students from four batches, namely the 2021, 2022, 2023, and 2024 batches. In this study, proportional stratified random sampling was used to select the sample, resulting in 191 students as respondents. The analysis showed that the level of academic procrastination was 67% in 128 students, and the level of self-control was 74.3% in 142 students, both of which were in the moderate category. In the hypothesis test, the correlation results showed that the variables of academic procrastination and self-control had a significant and negative correlation, with a correlation coefficient of -0.760 and a significance value of 0.000, which indicates < 0.05. This means that individuals with high self-control tend to have lower levels of academic procrastination, while individuals with low self-control tend to have higher levels of academic procrastination. These findings identify the importance of increasing self-awareness and self-regulation skills as efforts to reduce procrastination in the academic field.